Modern Approaches to Assessing the Universal Competencies of Future Teachers on the Example of the Communicative and Regulatory Component - A. V. Churakova (Открытое образование (Москва))
The purpose of the study. With the transition of higher education to modernized federal state educational standards of higher education, the concept of “universal competencies” was introduced in the theory of competency-based approach and in pedagogical practice. Later on, this notion was uniformly fixed by the levels of education for all areas of higher education in the Russian Federation. Federal state educational standards of higher education are focused on the norms of professional standards, and universal competencies supplement professional qualifications and reflect the peculiarities of educational training of future teachers. Today in Russia there is a stable social order for professional educators and formation of universal competences imposes new requirements to the quality of their training. According to the requirements of the federal state educational standards of higher education, the result of training is not only a competent specialist who is able to perform certain operations within his/her professional business, but also a specialist with a set of universal competences. However, the theory and practice of higher education currently lacks a unified approach to assessing the universal competencies of future teachers. The aim of the presented work is to identify modern approaches to the assessment of universal competencies in higher education institutions on the example of communicative and regulatory component of the universal competencies of future teachers.Materials and methods of research. The presented study comprehensively used such methods of research as study and analysis of scientific and pedagogical literature, normative and program documents of educational organizations of higher education, which form the basis of pedagogical activity, generalization of articles of major scientific and educational communities and their comparative analysis. The methodological basis of the study are integrated and activity-based approaches associated with the activity-based nature of the formation of universal competencies of future teachers.Results. As a result of the study, the theoretical foundations of evaluating universal competences are considered, the domestic and international experience of evaluating universal competences is analyzed and the evaluation of universal competences of future teachers is proposed on the example of the communicative and regulatory component.Conclusion. The federal state educational standards of higher education have a very detailed description of indicators of achieving universal competencies, but the present study highlights the problems of their assessment. The comparative analysis of domestic and international experience in assessing universal competencies showed that the results of individual research projects, as well as the opinions of employers and experts are a source of information on their formation. This indicates different approaches to assessing competencies. In order to assess universal competencies it is necessary to structure them. Our study is based on the three-component structure of universal competencies of future teachers, consisting of motivational, cognitive, communicative and activity-based components. The practical significance lies in the presentation of assessment of communicative and regulatory component of universal competencies of future teachers with the help of assessment tools for interim certification of the studied disciplines (modules) and various techniques.